A study on knowledge-based economy to business operation of Genting Mega Group - Abdul Murad, Mohd Azree (2001)
Genting Mega Group is a Bumiputera company. It consists of 5 subsidiaries that are Genting Mega Sdn. Bhd., Genting Mega Plantation Sdn. Bhd., Proivory Alliance Sdn. Bhd., Genting Mega Construction Sdn. Bhd. and Ratyh Corporation Sdn. Bhd. The company is involved in many business activities such as in plantation, general supply, property management, estate management, civil and construction, landscaping and transportation. The objectives of the company are to be excellent in producing quality products and providing services that can fulfill the client’s needs and demands. All of this is achieved through performing task through efficient, ethical, quality and professional management, financial stability in overcoming future competition and fulfilling Vision 2020. The aim of this research is to study the effectiveness and effects of Knowledge- Based Economy to the business operation done by Genting Mega Group. It also helps to measure and evaluate the important of Knowledge-Based Economy for today business in this new era of technology, especially to Genting Mega Group. Generally, their suppliers and clients are satisfied with the services provided by the company. Although they are satisfied with the services, it is important for the company to implement Knowledge-Based Economy to their business operation in order to be more efficient and effective. Through the implementation of the knowledge, it can help the company to improve telecommunication technology used, reduce cost and capital, and reduce labor shortages.